Analisis Pengaruh Kinerja Keuangan Dengan Analisis Rasio Terhadap Laba Perusahaan : (Studi kasus PT. Astra International TBK Periode 2010-2014) - Ismail; Khoiruddin; Betty Rahayu; Supriyanto; Muhammad Mudjib Musta’in (Journal of Public Power, 2019)
This research was perfomed to examine the effect of financial performance on the stock retun by automotive companies and components listed in the Indonesia Stock Exchange period 2010 - 2014. independent variable in this study is the Current Ratio, Debt to Equity Ratio, Total Asset Turn Over, and Return on Assets. While the dependent variable in this study is Stock Return. The sample in this study consisted of 17 auto and components companies listed on the Indonesia Stock Exchange from the period 2005 to 2011. The sampling technique used was purposive sampling criteria include: automotive companies listed on the Stock Exchange the period 2005 - 2011, provides financial statement data from the years 2005 - 2011, and the company has a complete financial statement data from 2005 to 2011. Data obtained from the publication ICMD 2011 and official website BEI (www.idx.co.id). The analysis technique used is multiple regression analysis. Hypothesis testing is performed with simultaneous F test and partial t test, with a significance level of 5%. The results of multiple regression analysis showed that the effect of simultaneous Current Ratio, Debt to Equity Ratio, Total Asset Turn Over, Return on Assets and Return on Stocks have significant impact. Effect of partial indicates that the Current Ratio no effect on Stock Return, Debt to Equity Ratio no effect on Stock Return, Total Asset Turn Over no effect on Stock Return, while Return on Assets Return Stock significant effect.